FORMAÇÃO FILOSÓFICA NA DIOCESE DE PONTA GROSSA: DILEMAS NA CONSTRUÇÃO DE UMA NOVA SUBJETIVIDADE ECLESIAL (Revista de História Regional, 2007)
This article intends to show some results of the monograph in History and Region, presented in the State University of Ponta Grossa in 1999, analyzing how the changes which happened in the Philosophy course, of the Institute of Philosophy and Theology Mater Ecclesiae (IFITEME) of Ponta Grossa Diocese, since it started in 1974(up to) until 1994, had been linked to different answers ofthe local Church to the intense eclesiastical, social and political transformations that pointed out to the emergency of a new religious subjectivity.